Analisis kinerja keuangan BPD DIY dan BPD BJB menggunakan analisis likuiditas, profitabilitas, dan solvabilitas - Valenty, Yola Andesta; Santoso, Fahrul Imam (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study describes the Financial Performance Analysis of PT Bank BPD DIY and PT BPD Jawa Barat and Banten Tbk by comparing financial performance in financial statements using analysis of liquidity ratios, profitability ratios, and solvency ratios in the 2016-2018 period. Both are companies owned by Regional Owned Enterprises (BUMD). PT Bank BPD DIY is a BUMD managed privately in its capital and share ownership, in contrast to PT BPD Jawa Barat and Banten Tbk, which have "go public" in share ownership managed openly. This study uses secondary data in the form of financial statements obtained from each company in balance sheets, income statements, cash flow statements, and other supporting data. This research method uses a descriptive method with a qualitative approach. The purpose of this study was to analyze the financial performance of the two companies viewed from the liquidity aspect to determine the extent to which the company could cover its current liabilities using current assets owned by each company. Then measure the performance of the two companies seen from the company's ability to generate profits in each accounting period. From these two aspects, it is also necessary to look at the solvency aspect by measuring the assets owned by the company by comparing it with all assets owned and the capital owned by a comparison of its liabilities. Then, from the two companies' measurements, a conclusion can be drawn. The results showed that the financial performance of the two companies went well from the analysis of liquidity, solvency, and profitability.